Compartment Syndrome Resulting from Carbon Monoxide Poisoning - Serbest, Sancar; Belhan, Oktay; Gurger, Murat; Tosun, Haci Bayram (Lippincott Williams & Wilkins, 2015)
Every year, especially in the cooler Fall and Winter months, hundreds of people die because of carbon monoxide poisoning. This occurs usually as an accident. It is a significant cause of poisoning worldwide. We present a case of compartment syndrome in both lower extremities with accompanying acute renal failure and systemic capillary leakage syndrome because of carbon monoxide poisoning.
Keywords: Acute-Renal-Failure; Oxygen-Affinity; Toxicity; Pressure; Shock